Effect of Gd addition on the activation energies of Bi-2223 superconductor - Erdem, M.; Öztürk, Özgür; Yücel, E.; Altıntaş, Sevgi Polat; Varilci, Ahmet; Terzioğlu, Cabir; Belenli, İbrahim (Elsevier BV, 2011)
Abstract We have investigated the effect of addition of Gd in Bi1.8Pb0.35Sr1.9Ca2.1Cu3GdxOy superconductor with x=0, 0.1, 0.2, 0.3, 0.4 and 0.5. The samples were prepared using the standard solid-state reaction method. The activation energies, irreversibility fields (Hirr), upper critical fields (Hc2) and coherence lengths at 0 K (ξ(0)) were calculated from the resistivity versus temperature (R–T) curves under DC magnetic fields up to 7 T. The superconducting transition temperature, Tc, and activation energy, U0, were found to decrease with increase in Gd concentration and with increase in applied magnetic field. The offset transition temperature of the pure (Gd00) sample without applied magnetic field is 108 K, whereas for Gd05 sample, the offset transition temperature drops to 5 K with 7 T applied magnetic field. The activation energy of the Gd00 sample without applied magnetic field is 34,980 K, and for Gd05 sample with 7 T applied field it is 98 K. Hirr and Hc2 values also decrease with increase in Gd addition. The possible reasons for the observed degradation in microstructural and superconducting properties due to Gd addition were discussed.
Keywords: BSCCO-2223; Rare Earth Addition; High Temperature Superconductors; Activation Energy; 7. Clean energy